Evolution of the dynamics of neutral superconductors between BCS and BEC regimes: the variational approach
We use variational approach to analyze the evolution of the dynamics of a neutral s-wave superconductor between BCS and BEC regimes. We consider 2D case, when BCS–BEC crossover occurs already at weak coupling and is governed by the ratio of the two scales — the Fermi energy EF and the bound state energy for two fermions in a vacuum, E0. BCS and BEC regimes correspond to EF >> E0 and EF